DAMPAK KOMUNIKASI PEMASARAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA PT. CAHAYA ALAM SEJATI - Fifi Dwi Pratiwi; Zuwina Miraza (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2019)
This research aims to determine the Effect of: (1) Marketing Communication on Costumer Loyalty of PT. Cahaya Alam Sejati, (2) Marketing Communication on Costomer Satisfaction of PT. Cahaya Alam Sejati, (3) Marketing Communication on Costumer Loyalty of PT. Cahaya Alam Sejati by Costumer Satisfaction as a mediating variable. This is a descriptive quantitative research. The research population is service costumer at PT. Cahaya Alam Sejati. The research sample is convenience sampling of 100 person. Primary data obtained from questionnaires, analysis techniques data used in this research is multiple regression analysis along the path analysis. Result of research indicate that: (1) Marketing Communication affect positively and significantly on Costomer Satisfaction of PT. Cahaya Alam Sejati, (2) Marketing Communication affect positively and significantly on Costumer Loyalty of PT. Cahaya Alam Sejati, (3) Costumer Satisfaction mediated the effect of Marketing Communikation on Costumer Loyality of PT. Cahaya Alam Sejati.